The design, synthesis and biological evaluation of novel barbiturate-based MMP inhibitors - Wang, Jun (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2010)
Matrix metalloproteinases (MMPs) are a group of Zn-dependent endopeptidases that participate in many diseases. Two MMPs, MMP-2 and MMP-9, which are especially associated with inflammatory diseases and tumor metastasis have been considered as promising target for arthritis, stroke, IBD, various pulmonary disorders and cancer. A great number of MMP inhibitors have been reported and are classified into different groups based on their structure, including hydroxamates, carboxylates, and thiols. Although some of these compounds exhibit great potency on inhibition of MMPs, their clinical trial results are disappointed due to lack of selectivity. Recently, appropriate C-5 substituted barbiturates have been found to show MMP inhibitory effects. Since barbiturates have been used as sedatives and hypnotics for decades and have well established clinical history, the MMP inhibitors we prepared were based on the structure of barbiturate.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin